TRANSLATING NON-EQIVALENT VOCABULARY FROM UZBEK INTO ENGLISH IN LITRARY TEXTS: CULTURAL AND DDIDACTIC APPROACHES (Ustozlar uchun, 2026)
Translating non-equivalent vocabulary from Uzbek into English poses significant challenges in literary translation due to linguistic, cultural, and contextual differences. This paper examines the strategies employed to convey culturally loaded or semantically unique Uzbek terms in English literary texts. The study applies a didactic and cultural approach, focusing on methods such as explicitation, paraphrasing, borrowing, and footnoting to retain meaning and stylistic features. Using a corpus of modern Uzbek literary works, the research analyzes translators’ choices and evaluates their effectiveness in conveying both denotative and connotative meanings. Findings indicate that non-equivalent vocabulary often requires adaptive translation strategies that balance fidelity to the source text with readability and cultural comprehensibility in the target language. The paper also discusses the implications of these strategies for translator training and pedagogy, highlighting the importance of cultural competence and contextual awareness. By integrating cultural and didactic perspectives, the study contributes to the broader field of literary translation and provides practical recommendations for handling non-equivalent terms in cross-cultural literary communication.